Pure electric and magnetic fields applied to reduced graphene oxide for defect repair and oxygen removal. (January 2021) - Miyata, Takeshi; Gohda, Syun; Fujii, Takashi; Ono, Hironobu; Itoh, Hibiki; Nishina, Yuta; Kashimura, Keiichiro
Abstract: The rapid repair of graphene oxide (GO) was demonstrated using a microwave cavity resonator that separates pure electric and magnetic fields from microwaves. Reduced graphene oxide (rGO), a high-quality graphene-like material, was obtained using our method. Raman spectroscopy of rGO after microwave treatment revealed that the D band intensity decreased as the temperature increased, while the G and G′ band intensities increased with increasing temperature. Furthermore, the cavity resonator provided better defect repair and oxygen removal from GO than conventional heating, and the microwave magnetic field yielded better quality rGO than the microwave electric field. Microwave heating removed surface impurities and repaired defects in GO more effectively than conventional heating, while suppressing graphitisation. These findings provide guidelines for the microwave-assisted reduction of GO for the fast and large-scale production of graphene. Graphical abstract: Image 1 Highlights: Microwave (MW) heating assessed for fast, large-scale reduction of graphene oxide MW electric and magnetic fields are separated for pure electric/magnetic heating MW heating gives better defect repair and oxygen removal than conventional heating MW magnetic field yields better results than MW electric field